A note on providing access to savings of VO members - Deeba, Farah; Ara, Ishrat (BRAC, 2019)
After joining a Village Organisation (VO) BRAC members are required to deposit weekly savings. Members have access to their savings any time after discontinuation of membership. Two recent studies earned out by the Research and Evaluation Division of BRAC indicates that this restrictive savings withdrawal practice has caused a number of dropouts. A concern for reducing and or preventing dropouts by meeting cash needs during times of hardship and protecting members rights to access their own savings are the two premises upon which this study is based. We argue that limiting members' access to their own savings (accounts) is counter to the fundamental objectives of BRAC. By providing members access to savings, BRAC can furnish them with a means of coping during their crisis and help to increase their sense of ownership over the VO. It is also hypothesized that access to savings will help make the members more responsible. We developed a scheme that would give members access to their savings under certain emergency conditions. The scheme is as follows: 20% of the previous years savings of each Village Organization will be set aside for savings loan. Members are allowed to withdraw savings as loans either in case of death/severe illness in the household or for post-disaster rebuilding. Savings loans must be repaid in monthly installments, within six months, with interest at a fixed rate of 6% per annum. The interest will be credited to individual loanee's savings account. BRAC will pay interest on the savings amount that remains after having disbursed the loan amount, in the individual loanee's account, while the loanee herself/himself will pay interest on the amount disbursed to her/him as savings loan. No member will be allowed to withdraw his/her entire savings amount. A member will be allowed to withdraw only 50% of the amount in excess of the matching savings percentage for an on-going general or program loan that the loanee may have taken. Overdue loanees will be ineligible to apply for the savings loan. Unless the savings loan has been repaid fully with interest, the loanee will not be qualified to apply for any other loans.